Traumatic brain injury - Vos, Pieter E.; Diaz-Arrastia, Ramon (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley Blackwell, 2015)
Traumatic Brain Injury provides practical, neurological guidance to the diagnosis and management of patients who suffer from traumatic brain injury. Taking a "patient journey" in traumatic brain injury, from prehospital management to the emergency department, into rehabilitation and finally reemergence in the community, it demonstrates how neurologists can facilitate recovery at all points along the way. It provides guidelines and algorithms to help support patients with brain injury within trauma centers, in posttraumatic care following discharge, and with mild traumatic brain injury not requiring immediate hospitalization. From an international team of expert editors and contributors, Traumatic Brain Injury is a valuable resource for neurologists, trainee neurologists, and others working with patients with traumatic brain injury.
The clinical problem of traumatic head injury / Ramon Diaz-Arrastia and Pieter E. Vos -- Neuroimaging in traumatic brain injury / Pieter E. Vos, Carlos Marquez de la Plata, and Ramon Diaz-Arrastia -- Out of hospital management in traumatic brain injury / Peter R.G. Brink -- Emergency department evaluation of mild traumatic brain injury / Noel S. Zuckerbraun, C. Christopher King, and Rachel P. Berger -- In-hospital observation for mild traumatic brain injury / Pieter E. Vos and Dafin F. Muresanu -- ICU care : surgical and medical management : indications for immediate surgery / Peter S. Amenta and Jack Jallo -- ICU Care : surgical and medical management : neurological monitoring and treatment / Luzius A. Steiner -- ICU Care : surgical and medical management : systemic treatment / Lori Shutter -- Rehabilitation of cognitive deficits after traumatic brain injury / Philippe Azouvi and Claire Vallat-Azouvi -- Epidemiology of traumatic brain injury / Ramon Diaz-Arrastia and Kimbra Kenney -- Neuropsychiatric and behavioral sequelae / Kathleen F. Pagulayan and Jesse R. Fann -- Follow-up and community integration of mild traumatic brain injury / Joukje van der Naalt and Joke M. Spikman.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Brain -- Wounds and injuries -- Treatment; Traumatology; Brain Injuries -- diagnosis; Brain Injuries -- therapy; Medical; MEDICAL -- Surgery -- General; Brain -- Wounds and injuries -- Treatment; Traumatology; Electronic books